Landslide Potential Investigation for Disaster Risk Reduction in Central Bengkulu Regency, Bengkulu Province, Indonesia - Arif Ismul Hadi; Refrizon Refrizon; Muchammad Farid; Budi Harlianto; Julia Inti Sari (Indonesian Journal on Geoscience, 2021)
DOI:10.17014/ijog.8.3.313-328Bengkulu Province is the converging path region between the Indo-Australian - Eurasian tectonic plates in the ocean and the Sumatran f ault crossing on the mainland. The condition implies that the sliding force of the slab is easy to trigger fractures and to cause the material to be relatively less elastic, resulting in high seismic intensity. This study aims to identify areas with the potential for landslides and its mapping, and to analyze the factors that cause landslides in Central Bengkulu Regency, Bengkulu Province, Indonesia. This study was conducted using rock physical parameters of ground shear strain (GSS) which were correlated with parameters of slope, slope height, Vs30 value, fault distance to measurement point, rock conditions, rainfall, and PGA value. Furthermore, these parameters were overlaid thoroughly by the statistical method of the Analytical Hierarchy Process (AHP). Data acquisition is divided into two stages, namely the secondary data collection stage and the field survey stage. Secondary data collection was carried out to support the creation of landslide potential maps, analysis, and field survey data input. Secondary data is the value of Vs 30, the distance of the fault to the measurement point, rainfall, and the PGA value. Field survey data are in the form of GSS values, slope, slope height, and rock conditions. The results of this study are identified areas that have the category of high, medium, and low landslide potential. Based on the calculated parameters, the GSS parameter is the most dominant which affects the landslide potential in the studied area.